Cues play a critical role in estrous cycle-dependent enhancement of cocaine reinforcement - Johnson, Amy R.; Thibeault, Kimberly C.; Lopez, Alberto J.; Peck, Emily G.; Sands, L. Paul; Sanders, Christina M.; Kutlu, Munir Gunes; Calipari, Erin S. (Neuropsychopharmacology (New York, N.Y.), 2019)
While preclinical work has aimed to outline the neural mechanisms of drug addiction, it has overwhelmingly focused on male subjects. There has been a push in recent years to incorporate females into existing addiction models; however, males and females often have different behavioral strategies, making it important to not only include females, but to develop models that assess the factors that comprise female drug addiction. Traditional self-administration models often include light or tone cues that serve as discriminative stimuli and/or consequent stimuli, making it nearly impossible to disentangle the effects of cue learning, the cues themselves, and acute effects of psychostimulant drugs. To disentangle the interaction between drug-associated cues and the consummatory and appetitive responding driven by cocaine, we have developed a new behavioral procedure that combines Pavlovian-instrumental transfer with behavioral economic analysis. This task can be completed within a single session, allowing for studies looking at estrous cycle stage-dependent effects in intact cycling females, something that has been difficult in the past. In this study, we found no differences in self-administration across the estrous cycle in the absence of cues; however, when cues were introduced, the cues that acquired value during estrus-but not during diestrus or in males-increased motivation. Cues paired during estrus also increased c-fos expression to a greater extent in striatal regions, an effect that may underlie the observed increases in seeking induced by these cues, even weeks later. Together, these data suggest that fundamental differences in the motivational properties of psychostimulant drugs between males and females are complex and are driven primarily by the interaction between drug-associated stimuli and drug effects.